what is the answer of following eqation by elimination method?

Asked by Shivraj Raghu | 9th May, 2013, 10:18: PM

Expert Answer:

4x-3y=8 (1)
6x-y=29/3 (2)
Multiplying the second equation with 3
18x - 3y = 29

Subtracting this equation from the first one
 
14x = 21
x = 3/2 
Hence, subsituting the value of x in equation 1
4(3/2) -3y = 8
6-8 = 3y
y = -2/3 

Answered by  | 10th May, 2013, 04:59: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.